Benefits of the 5’s methodology in the Manufacturing Industry: A literature review 2017-2022 (LACCEI, 2024)
This literature review proposes to describe the benefits of implementing the 5's in the manufacturing industry, for this purpose 50 articles from journals indexed to databases such as Scopus, Latindex, Crosreff, Ebsco, Dialnet, Redalyc, among others, which were published in English and Spanish, and between the years 2017 and 2022. From the content analysis it was established that the implementation of the methodology in all cases improves productivity, in addition to improving the safety of the work environment, reduces costs, accident rate, improves human relations at work, increases commitment and promotes a friendly work environment. Likewise, it has been included as the main tool and base for the implementation of Lean Manufacturing and TPM, but it interacts very well with other tools such as Warehouse Management, Kayzen, SMED, Work Study, Layout, VSM, SIPOC among others.